#1**0 **

Is this what you mean? 2sin2x=-sqrt(3)???. if so, then:

Solve for x:

2 sin(2 x) = -sqrt(3)

Divide both sides by 2:

sin(2 x) = -sqrt(3)/2

Take the inverse sine of both sides:

2 x = (4 π)/3 + 2 π n_1 for n_1 element Z

or 2 x = (5 π)/3 + 2 π n_2 for n_2 element Z

Divide both sides by 2:

x = (2 π)/3 + π n_1 for n_1 element Z

or 2 x = (5 π)/3 + 2 π n_2 for n_2 element Z

Divide both sides by 2:

Answer: |

|** x = (2 π)/3 + π n_1 for n_1 element Z or x = (5 π)/6 + π n_2 for n_2 element Z**

Guest Feb 16, 2017